Explaining regional economic multipliers of tourism: does cross-regional heterogeneity exist?. Issue 1 (2nd January 2018) - Yang, Yang; Fik, Timothy J.; Altschuler, Benjamin
ABSTRACT: This study investigates the determinants of tourism-related economic multipliers, which are calibrated from regional input–output tables of 30 Chinese provinces. Several latent class regression models are applied to capture cross-regional heterogeneity and investigate the determinants of output, income, and employment multipliers. Results indicate that the level of economic development is positively associated with output multiplier, and it is also positively associated with employment multiplier when the multiplier is large. Moreover, the size of tourism economy is negatively associated with employment multiplier when the multiplier is small. Some policy implications are presented based on empirical results.